Pendampingan Penerapan Game Edukasi Berbantuan Breshna IO bagi Guru-Guru di SDN Tanjungsari - Janattaka, Nugrananda; Satria, Aditya Pringga; Oktaviarini, Nourma (Universitas Pahlawan Tuanku Tambusai, 2026)
In the development of learningin the 21st century, teachers are required to be able to provide interactive, creative, and easily accessible learning media for students. Breshna.io, as a platformfor creating educational games without coding, offers a practical solution for teachers to produceinteresting learning media that suits the needs of the material. This community service activityaims to improve the competence of teachers atSDN 1 Tanjungsari in utilising learning technology throughguidance on the application of educational games assisted by Breshna.io. The implementation methodincludes socialisation, technical training, guidance on creating educational games, and evaluation of the results of implementation in the teaching and learning process. This activityinvolves all teachers as active participants, with a hands-on approach. The results of the activity through the response form showan increase in teachers' ability to design and develop educational games, as well as an increase in teachers' motivation to integrate technologyinto learning